2022
DOI: 10.3171/2021.10.jns212393
|View full text |Cite
|
Sign up to set email alerts
|

Does tamsulosin decrease postoperative urinary retention in spine surgery? A double-blind, randomized controlled trial

Abstract: OBJECTIVE The authors’ objective was to determine whether preoperative administration of tamsulosin decreases postoperative urinary retention after spine surgery. METHODS In this randomized, double-blind, placebo-controlled clinical trial performed at a single institution between 2016 and 2019, eligible males aged 50 to 85 years were administered tamsulosin or placebo for 5 days prior to elective spine surgery. Patients were excluded if they were taking alpha adrenergic blocking drugs; were allergic to tamsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…Fifteen studies did not meet eligibility criteria. Five studies 10 , 11 , 0–2 were identified for qualitative and quantitative syntheses ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fifteen studies did not meet eligibility criteria. Five studies 10 , 11 , 0–2 were identified for qualitative and quantitative syntheses ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five RCTs 10 , 11 , 1–3 included 878 patients (α1-antagonist, 434; placebo, 444) who were enrolled between 1987 and 2019 ( Table 1 ). Of the five RCTs, three 11 , 21 , 22 involved patients receiving primary arthroplasty and two 10 , 20 involved patients undergoing elective spine surgery. In the study by Petersen et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies reported the data of adverse events, and the pooled analysis showed that tamsulosin administration was associated with a higher risk of adverse events [57/688 (8.3%) vs. 33/624 (5.3%); RR = 1.68; 95% CI: 1.13–2.48; P = 0.010; heterogeneity: I 2 = 33%; P = 0.20] ( 23 25 , 37 , 39 ) ( Figure 7 ). Dizziness and vomiting were the most frequently described adverse events, with a total of 15 episodes.…”
Section: Resultsmentioning
confidence: 99%
“…In the contrast, the randomized control trial (RCT) by Schubert et al observed no statistical significance in the rate of POUR whether tamsulosin was administrated or not ( 24 ). Given that there were also other publications with uncertain results ( 25 , 26 ), the evaluation of the prophylactic efficacy of tamsulosin against POUR in male patients is still of interest and subject to discussion. The present systematic review and meta-analysis aimed to evaluate the prophylactic efficacy of tamsulosin against POUR in male patients.…”
Section: Introductionmentioning
confidence: 99%